Pepita Disco PPM : margins and elasticity - Hennessy, Julie, (SAGE knowledge. Cases., 2016)
Carolina Araujo had recently taken control of her family's business, Pepita Disco PPM, Uruguay's second-largest producer of beef-based dog food, treats, and toys. While she respected the company's nearly eighty-year history, Carolina felt that Pepita Disco had grown complacent with its market share and was basically preserving the status quo. Her plan was to re-energize the employee base and grow Pepita Disco's business faster than the overall market. This exercise poses a fictional problem about a company's efforts to predict the impacts of price, product cost, and spending moves on profitability.